PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS HOTS SISWA KELAS VIII SMPN 10 MERANGIN - Puji Hartatik; Ade Susanti; Sukur (Pendidikan Matematika | STKIP YM Bangko, 2022)
This research purposed to produce a valid, practical and effective HOTS-based student worksheet (LKPD). This research uses an R&D research method with a 4-D development model, in which consists of the define, design, development and disseminate stages. HOTS-based worksheets validated by 5 validators, 3 material expert validators, 1 linguist validator and 1 media expert validator. After validation, the research phase was carried out in class VIIIC of SMPN 10 Merangin with a total of 28 students. The results of the LKPD validation obtained an average of 4.36, so it can be categorized as very valid. As well as from the results of the research obtained the results of practicality and product effectiveness. Practicality of LKPD obtained a percentage of 78.01% in the practical category. Meanwhile, for effectiveness in terms of student learning achievement, the percentage of completeness reached 82.15% and in terms of students’ activity, the percentage of students was 91.17%, which means very active. Thus, it can be concluded that the HOTS-based LKPD was valid, practical and effective.